Knowledge management initiatives for SIRIM Berhad / Siti Nuur-Ila Mat Kamal and Zainab Sulaiman - Mat Kamal, Siti Nuur-Ila; Sulaiman, Zainab (2012)
In the past two years, there has been growing interest in knowledge management, as evidenced by the large attendance at national conferences and seminars in Malaysia. Knowledge management concepts have become more widely accepted and understood. An organization that initiates and implements an effective knowledge management program should see benefits to their organization. The objective of this study is to identify the level of awareness on KM practices at SIRIM Berhad and to establish and provide a KM framework to initiate KM in the organization. Questionnaires have been distributed to the staff at SIRIM Berhad. The analysis indicated that staff understanding and awareness of KM is important to successfully implement KM initiative in the organization, KM has been practices in the current working environment to support business process in the organization and the usage of information and communication technology (ICT) is the most significant tools towards successful implementation of knowledge management in the organization. The findings are found to help the organization in implementing KM initiatives from the KM model that has been suggested.